Contact X-ray Brachytherapy as a sole treatment in selected patients with early rectal cancer – Multi-centre study - Ngu Wah Than; D. Mark Pritchard; David M. Hughes; Kai Shing Yu; Helen S. Minnaar; Amandeep Dhadda; Jamie Mills; Joakim Folkesson; Calin Radu; C.A. Duckworth; Helen Wong; Muneeb Ul Haq; et al. (Clinical and Translational Radiation Oncology, 2024)
Background and purpose: Radical surgery is the standard of care for early rectal cancer. However, alternative organ-preserving approaches are attractive, especially in frail or elderly patients as these avoid surgical complications. We have assessed the efficacy of sole Contact X-ray Brachytherapy (CXB) treatment in stage-1 rectal cancer patients who were unsuitable for or declined surgery. Materials and methods: This retrospective multi-centre study (2009–2021) evaluated 76 patients with T1/2-N0-M0 rectal adenocarcinomas who were treated with CXB alone. Outcomes were assessed for the entire cohort and sub-groups based on the T-stage and the criteria for receiving CXB alone; Group A: patients who were fit enough for surgery but declined, Group B: patients who were high-risk for surgery and Group C: patients who had received prior pelvic radiation for a different cancer. Results: With a median follow-up of 26(IQR:12–49) months, initial clinical Complete Response (cCR) was 82(70–93)% with rates of local regrowth 18(8–29)%, 3-year actuarial local control (LC) 84(75–95)%, distant relapse 3 %, and no nodal relapse. 5-year disease-free survival (DFS) and overall survival (OS) were 66(48–78)% and 58(44–75)%. Lower OS was observed in Groups B [HR:2.54(95 %CI:1.17, 5.59), p = 0.02] and C [HR:2.75(95 %CI:1.15, 6.58), p = 0.03]. Previous pelvic radiation predicted lower cCR and OS. The main toxicity was G1-2 rectal bleeding (26 %) and symptoms of impaired anal sphincter function were not reported in any patients. Conclusion: CXB treatment alone achieved a high cCR rate with satisfactory LC and DFS. Inferior oncological outcomes were observed in patients who had received prior pelvic radiotherapy. CXB alone, with its favourable toxicity profile and avoidance of general anaesthesia and surgery risks, therefore, can be considered for patients who are unsuitable for or refuse surgery.